Monitoring the population and distribution of the proboscis monkey (Nasalis larvatus) in the Klias Peninsula, Sabah, Borneo, Malaysia: Insights from an 18‑year study - Henry Bernard; Sharifah N. H. B. Mohammad‑Shom; Menaga Kulanthavelu; John C. M. Sha; Titol P. Malim; Nicola K. Abram; Ikki Matsuda (Springer Verlag, 2025)
Long-term monitoring data on population abundance and distribution are essential for developing and refining conservation strategies, particularly for endangered species like the proboscis monkey (Nasalis larvatus), for which data remain limited across much of their range in Borneo. Previous studies conducted in 2004/2005 and 2014 in the Klias Peninsula, western Sabah, northern Borneo, provided important insights into population trends and distribution. Building on this foundation, we reassessed the proboscis monkey population in 2022 after an 8-year interval and investigated changes in land use and land cover during the same period. Our findings indicate a lower overall estimate of population abundance (number of individuals); however, the number of observed groups is comparable to previous studies, suggesting some stability. Distribution patterns have remained relatively stable, with population strongholds in the central part of the Klias Peninsula, underscoring the continued importance of areas like Padas Damit Forest Reserve for proboscis monkey conservation. Our data also reveal concerning trends, including a decline in group sizes (number of individuals per group) within breeding units and the presence of very small populations in fragmented sites such as Bongawan, presenting ongoing conservation challenges. Our land-use and land-cover change findings further revealed that less than half of the available proboscis monkey habitats in this region are fully protected. Vegetation analysis showed that tree species richness positively influences proboscis monkey abundance, emphasizing the critical role of food resource diversity. These findings have important conservation implications for the long-term survival of this endangered primate in the Klias Peninsula region.